2008
DOI: 10.1111/j.1600-079x.2008.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐9 and metalloproteinase‐2 activity and expression is reduced by melatonin during experimental colitis

Abstract: Matrix metalloproteinases (MMPs) are associated with matrix turnover in both physiological and pathological conditions. Several data indicate that MMPs play an important role in the pathogenesis of colitis. Various evidence has documented that the pineal secretory product melatonin exerts an important anti-inflammatory effect in different experimental models including colitis. However, no reports are available on the relationship between the activity and expression of MMPs and anti-inflammatory effect of melat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 68 publications
(81 reference statements)
2
31
0
Order By: Relevance
“…Furthermore, it has been shown that MMP-9 is the most abundantly expressed proteinase in IBD. MMP-9 is suggested to be an essential factor for mucosal damage in IBD, as MMP-9 mediates tissue damage during intestinal inflammation [26,27,28,29,30,31,54,55]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that MMP-9 is the most abundantly expressed proteinase in IBD. MMP-9 is suggested to be an essential factor for mucosal damage in IBD, as MMP-9 mediates tissue damage during intestinal inflammation [26,27,28,29,30,31,54,55]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the MMPs, MMP-3 and MMP-9 are consistently upregulated in the animal models of colitis [28,29,30,31]. We and others have reported that MMPs, particularly MMP-9 (type IV collagenase – gelatinase B), is especially important not only in the process of GI tumor progression, but also in the inflammatory and remodeling processes in IBD [32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are involved in the development processes of experimental colitis (Esposito et al 2008b), endometriosis (Paul et al 2008), liver injury (Mishra et al 2011), traumatic experimental spinal cord injury (Esposito et al 2008a), acute ischemic stroke (Ramos-Fernandez et al 2010), and neurodegenerative diseases (Reyes et al 2009, Rosenberg 2009, Bauer et al 2010. Meanwhile, many studies also show that MMPs have contributed to tumor invasion, metastasis, and angiogenesis (Toth & Fridman 2001, Zhang et al 2003, Kessenbrock et al 2010, Pratheeshkumar & Kuttan 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that reduced MMP-9 and MMP-2 activities are associated with lower expression of TNF-α [3]. Cuzzocrea et al also showed that melatonin monotherapy significantly reduced the appearance of diarrhea and the reduced body weight in rats induced colitis, the effect is mediated by decreasing the production of TNF-α, reducing the activation of NF-κB, decreasing the expression and activity of MMP-9 and -2, and the antiapoptotic effect of melatonin [41].…”
Section: Abdulridhamentioning
confidence: 96%